Penjernih Kabut Asap Kebakaran Hutan dengan Media Plasma dan Karbon Aktif Terintegrasi - Isnan, Muhammad; Rofiq, Ainur; Hasanudin, Ibnu Awal; Thoharudin, Thoharudin (Semesta Teknika, 2018)
Smoke haze from forest fires consists of Volatile Organic Compounds (VOC) and particulate matter which has micro size that can cause the respiratory disorders. Therefore, the device to reduce the matters is necessary to prevent the respiratory health including the lung. One of the many methods is using plasma and activated carbon for eliminating the matters from the air that was conducted in this study. Smoke haze was modeled as exhaust gas obtained from rice husk combustion. The velocity of gas in the cleaning device was controlled in various velocities, namely 0.3, 0.9, 1.2 and 1.5 m/s. The calculation of smoke haze particulate matter and VOC was conducted in a simple method by using cutton as filter media to separate the particulate matter and VOC from the gas. This study resulted that the increasing of velocity affected the increasing of particulate matter and VOC filtered on the cutton. The plasma utilisation on the device affected the reduction of particulate matter and VOC filtered on the cutton. The application of both plasma and activated carbon in the device could achieve the best performance of eliminating the particulate matter and VOC indicated by the clean cutton obtained after filtering. The highest efficiency of particulate matter and VOC removal was achieved by applicating both plasma and activated carbon with gas velocity of 1.5 m/s, namely 96.1 %.